Sleep Deprivation and Caffeine Treatment Potentiate Photic Resetting of the Master Circadian Clock in a Diurnal Rodent - Jha, Pawan Kumar (J Neurosci, 2017)
Circadian rhythms in nocturnal and diurnal mammals are primarily synchronized to local time by the light/dark cycle. However, nonphotic factors, such as behavioral arousal and metabolic cues, can also phase shift the master clock in the suprachiasmatic nuclei (SCNs) and/or reduce the synchronizing effects of light in nocturnal rodents. In diurnal rodents, the role of arousal or insufficient sleep in these functions is still poorly understood. In the present study, diurnal Sudanian grass rats, Arvicanthis ansorgei, were aroused at night by sleep deprivation (gentle handling) or caffeine treatment that both prevented sleep. Phase shifts of locomotor activity were analyzed in grass rats transferred from a light/dark cycle to constant darkness and aroused in early night or late night. Early night, but not late night, sleep deprivation induced a significant phase shift. Caffeine on its own induced no phase shifts. Both sleep deprivation and caffeine treatment potentiated light-induced phase delays and phase advances in response to a 30 min light pulse, respectively. Sleep deprivation in early night, but not late night, potentiated light-induced c-Fos expression in the ventral SCN. Caffeine treatment in midnight triggered c-Fos expression in dorsal SCN. Both sleep deprivation and caffeine treatment potentiated light-induced c-Fos expression in calbindin-containing cells of the ventral SCN in early and late night. These findings indicate that, in contrast to nocturnal rodents, behavioral arousal induced either by sleep deprivation or caffeine during the sleeping period potentiates light resetting of the master circadian clock in diurnal rodents, and activation of calbindin-containing suprachiasmatic cells may be involved in this effect. SIGNIFICANCE STATEMENT Arousing stimuli have the ability to regulate circadian rhythms in mammals. Behavioral arousal in the sleeping period phase shifts the master clock in the suprachiasmatic nuclei and/or slows down the photic entrainment in nocturnal animals. How these stimuli act in diurnal species remains to be established. Our study in a diurnal rodent, the Grass rat, indicates that sleep deprivation in the early rest period induces phase delays of circadian locomotor activity rhythm. Contrary to nocturnal rodents, both sleep deprivation and caffeine-induced arousal potentiate the photic entrainment in a diurnal rodent. Such enhanced light-induced circadian responses could be relevant for developing chronotherapeutic strategies.